Cyclopentane derivatives - COFFEE; EDWARD C. J; CATON; MICHAEL P. L; WATKINS; GORDON L (1982)
Cyclopentane derivatives of the formula: wherein R1 represents hydrogen or a carboxylic acyl group, and either (i) R2 represents a group of the formula: -CR3R4R5 II (wherein R3 and R4 represent hydrogen or alkyl, and R5 represents hydrogen, or alkyl, alkoxy, cycloalkyl or adamantyl, or R5 represents alkyl substituted by alkoxy, or by cycloalkyl or by adamantyl, or the group -CR3R4R5 together forms a cycloalkyl or adamantyl group), X represents trans-vinylene or ethylene and Y represents carbonyl or a group of the formula: III wherein R6 represents hydrogen or alkyl, and R7 represents hydrogen or a carboxylic acyl group, or else (ii) R2 represents a group of the formula: -A-Z-R8 IV (wherein A represents alkylene, Z represents a direct bond or oxygen or sulphur, and R8 represents an aryl or heterocyclyl group which may be substituted by one or more of halogen, alkyl, alkoxy and trihalomethyl), X in formula I represents ethylene or trans-vinylene and Y in formula I represents carbonyl or a group of formula III, or else (iii) R2 represents a group R8 and X and Y in formula I represent simultaneously ethylene and carbonyl, trans-vinylene and carbonyl, or ethylene and -CH(OR7)- groups respectively. The compounds are new and possess pharmacological properties similar to those of prostaglandins.